Bakun damned: Extinguishment of native customary land that went topsy-turvy? - Kamarudin, Abdul Rani (Penerbit UMT, Universiti Malaysia Terengganu, 2016)
The development of the massive hydro-electricity Bakun dam in Central Borneo or in the central region of Borneo, namely in “Sarawak” was not without problems. The development of the Bakun dam that completed only recently but was initiated in early 1990 involved the extinguishment of vast areas of the Natives’ Communal Customary Land of the Baluy Region designated to be flooded and the consequent mandatory compensation to those natives affected by the development of the dam. This paper discussed the laws involved and consequently addressed issues such as whether the extinguishment was valid or otherwise in terms of its land valuation, claimants, compensation disputes, validation of claims and the natives’ vested rights over their customarily lands purportedly extinguished. It was the lack of understanding of the natives’ origins and customs, their inherent rights over their ancestral communal lands that were the main causes for the setbacks faced by the State Government in its purported extinguishment of the natives’ communal ancestral lands.